Characterization of Natural Killer Cells and Cytokines in Maternal Placenta and Fetus of Diabetic Mothers - Hara, Cristiane De Castro Pernet [UNESP]; Franï¿½a, Eduardo Luzï¿½a; Fagundes, Danny Laura Gomes; De Queiroz, Adriele Ataides; Rudge, Marilza Vieira Cunha [UNESP]; Honorio-Franï¿½a, Adenilda Cristina; Calderon, Iracema de Mattos Paranhos [UNESP] (Hindawi, 2016)
The present study characterized natural killer cells and cytokines in diabetic mothers, their placenta, and fetus. In the maternal blood from the hyperglycemic groups, the CD16+CD56- NK cells increased, whereas that of CD16+CD56+ decreased in gestational diabetes mellitus [GDM] group. Cord blood from type 2 diabetes [DM-2] showed a higher proportion of CD16+CD56- and CD16-CD56+. The placental extravillous layer of GDM and DM-2 showed an increase of CD16+CD56- cells and, irrespective of region, the proportion of CD16-CD56+ cells was higher in mild gestational hyperglycemia [MGH] and GDM and lower in DM-2. IL-2 was lower in maternal blood and IFN-γ higher in maternal and cord blood from the GDM group. IL-17 was higher in maternal and cord blood from the DM-2 group. The placental extravillous layer of the MGH showed high levels of IL-4, IL-6, IL-10, IL-17, and IFN-γ and low levels of IL-1β and IL-8, whereas the placental villous layer contained high levels of IL-17 and IFN-γ. The GDM group, irrespective of region, showed higher levels of IL-8. The DM-2 group, irrespective of region, placenta showed high levels of TNF-α, IL-17, and IFN-γ. The hyperglycemia produces an inflammatory environment with a high content of inflammatory cytokines and cells expressing CD16+.